PANCOAST TUMOR PRESENTING WITH HORNER SYNDROME: A CASE REPORT - Raden Andi Ario Tedjo; Hillary Hillary; Vivienne Tjung; Stefanus Erdana Putra; Muhammad Hafizhan (MNJ (Malang Neurology Journal), 2023)
Case Report: A 50-year-old man was referred to Dr. Moewardi General Hospital with history of right chest pain that radiate to the right back and hand for 2 months. His complaint did not improve with medication and physical therapy. On physical examination we observed multiple nodules on the right axilla, scapula, and colli region. Neurological examination revealed right sided partial ptosis, anisocoria, ipsilateral weakness, and ipsilateral allodynia, and anhidrosis T1 dermatome. CT-scan showed a right lung mass in the superior lobe of the apical segment. The diagnosis of Horner syndrome is then established caused by multiple lymphadenopathies. His symptoms then relieved after lymphadenectomy. Conclusion: Horner syndrome, characterized by ipsilateral pupillary anisocoria, ptosis and anhidrosis, is one of the complications of Pancoast tumor invasion to the sympathetic nervous system in the C8, T1, and T2 nerve territory.